(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Spontaneous Coronary Artery Dissection (SCAD) is a rare defect in the coronary artery wall due to tear in the coronary arterial wall, which may lead to heart muscle ischemia and important cause of acute myocardial infraction and sudden cardiac death. It mostly common in young female but also occurs in male. The exact aetiology of Spontaneous Coronary Artery Dissection (SCAD) is unknown but associated with some risk factors. Prompt diagnosis and management is necessary to prevent sudden death. Invasive coronary angiography is the main diagnostic modality and treatment options ranges from conservative to percutaneous intervention or a surgical procedure. JCMCTA 2023 ; 34 (1) : 149-154